UMP, Thailand Universities to work together - Norhidayah, Mohamad (2018)

(untitled)
Kuantan, 19 January – Universiti Malaysia Pahang is looking forward to work closely with Thailand academic institutions in areas of academic network programme, focusing on UMP dual degree with German academic institutions and students exchange programme between UMP and universities in Thailand.